2013
DOI: 10.1016/j.rmcr.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic respiratory failure from tuberculosis pneumonia: Survival after prolonged extracorporeal membrane oxygenation support

Abstract: Tuberculosis (TB) is an uncommon cause of severe respiratory failure, even in highly endemic regions. Mortality in cases requiring mechanical ventilation (MV) varies between 60 and 90%. The use of extracorporeal membrane oxygenation (ECMO) is not frequently needed in TB. We report the case of a 24 year old woman diagnosed with bilateral pneumonia that required MV and intensive care, patient was managed with prone ventilation for 48 h, but persisted in refractory hypoxemia. Etiological study was only positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Andresen et al. similarly reported that systemic corticosteroid therapy during ECMO support led to progressive improvement of respiratory function [14] . Several other studies have also suggested the effectiveness of adjunctive use of corticosteroids for PTB [19] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Andresen et al. similarly reported that systemic corticosteroid therapy during ECMO support led to progressive improvement of respiratory function [14] . Several other studies have also suggested the effectiveness of adjunctive use of corticosteroids for PTB [19] , [20] , [21] .…”
Section: Discussionmentioning
confidence: 98%
“…The mortality of ARDS patients with PTB requiring MV is relatively high compared with that of patients with ARDS from other causes [9] . Five patients with acute respiratory failure due to PTB were recently reported to be successfully rescued by ECMO [10] , [11] , [12] , [13] , [14] , [15] ( Table 1 ). Given the high mortality rate of ARDS patients with PTB, ECMO could be an important treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion 31 (4) After cannulation, the invasiveness of the mechanical ventilation was reduced to facilitate lung healing. Tidal volume (4 ml/kg ideal body weight), positive endinspiratory pressure (less than 28 mmHg) and FiO 2 were decreased.…”
Section: Vv Ecmo; Awake Ecmo; Tuberculosis; Trauma; Spontaneous Breatmentioning
confidence: 99%
“…2 The treatment of TB patients with ECMO has been described, although TB-induced severe lung failure is rare. 3,4 Less than 5% of TB patients require mechanical support. 5 Extracorporeal lung support provides time for lung recovery when it is administered in combination with adequate therapy for the underlying disease.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2016 Extracorporeal Life Support Organization (ELSO) registry report, the average duration of V-V ECMO in adults with acute respiratory failure is 10.5–13.5 days [ 1 ]. Some patients whose lung damage is not improved may require support of V-V ECMO for more than 2 weeks, and recently, there have been more reports of prolonged V-V ECMO [ [2] , [3] , [4] , [5] , [6] , [7] , [8] ]. However, we do not know how long it is feasible to wait for native lung recovery or lung transplant (LTx) with the use of ECMO.…”
Section: Introductionmentioning
confidence: 99%